The Role of Two-Way Communication in Institutional Resilience During the COVID-19 Crisis: A Global Perspective - Hutagalung, Maasyithah; Sutrisno, Tri (Communica : Journal of Communication, 2025)
Crisis communication has become an essential function of public institutions, particularly in light of recent global disruptions such as the COVID-19 pandemic. This narrative review investigates effective communication strategies and recurrent failures in public crisis response, aiming to uncover key factors that enhance or hinder institutional trust. A structured literature review was conducted across Scopus, Web of Science, PubMed, and Google Scholar, using targeted keywords such as "crisis communication," "public institutions," "risk communication," and "social media trust." Inclusion criteria emphasized peer-reviewed empirical studies and reviews that addressed communication practices during crises. The review highlights the importance of two-way communication, which fosters public trust by encouraging active engagement and feedback. Social media emerges as a double-edged sword—while it facilitates rapid information dissemination, it also accelerates the spread of misinformation. Studies show that content featuring emotional appeal, cultural relevance, and empathy improves message reception. However, systemic barriers like resource constraints and institutional mistrust remain persistent obstacles. Findings suggest that adaptive, emotionally resonant communication, combined with transparent messaging and inter-agency collaboration, significantly improves crisis response. Public institutions must therefore develop strategies that integrate digital tools, empower local leaders, and prioritize audience-specific messaging. These insights offer a foundation for future policies and research aimed at strengthening institutional resilience in the face of ongoing and emerging crises.